WiMax Operator’s Manual Building 802.16 Wireless Networks (Second Edition) - Sweeney, Daniel (Apress, 2013)
This book provides the background in broadband wireless fundamentals, packet data, and overall network operation and management to enable a network operator to set up a network with standards-based equipment and to run it profitably thereafter. It is an operational handbook rather than an engineering text, and it is highly practical rather than theoretical. Technical discussions that occur are always in reference to addressing the realworld problems involved in running a network and serving the customer base. There are no tutorials on radio frequency propagation or digital modulation techniques; rather, the emphasis is on using technology to deliver specific services to specific types of customers.